Pengaruh model creative problem solving terhadap kemampuan memecahkan masalah dan motivasi belajar pada mata pelajaran Geografi - Fadalena, Triya; Sahrina, Alfi; Aini, Zubaidah Nur (Universitas Negeri Malang, 2025)
The effect of the creative problem solving model on problem solving ability and learning motivation in Geography subjects Geography learning is contextual and focuses on issues related to the life of the surrounding environment. Problem-solving abilities and low student learning motivation are problems in geography learning. This research aims to determine the influence of the creative problem-solving model on problem-solving abilities and learning motivation in geography subjects at Kepanjen Islamic High School. This type of research is a quasi-experiment with a pretest and posttest control group design covering classes X-2 and X-4, sampling using purposive sampling. The data analysis used is prerequisite testing and hypothesis testing. Hypothesis testing was used the MANOVA (Multivariate Analysis of Variance) Test. Based on the analysis results, the average score for the experimental class was higher than that of the control classes. The MANOVA test results show that the F value for Pillai’s trace, Wilks’ lambda, Hotelling’s trace, and Roy’s Largest Root have the same value, meaning that the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. The findings in this research are that the syntax of the creative problem-solving model, namely problem finding, idea finding, and solution finding, influences problem-solving abilities and learning motivation. The conclusion of this research shows a significant influence of the creative problem-solving learning model on the problem-solving abilities and learning motivation of students who are given treatment and those who use conventional learning models. Pembelajaran geografi bersifat kontekstual dan berfokus pada persoalan-persoalan yang berkaitan dengan kehidupan lingkungan sekitar. Kemampuan memecahkan masalah dan motivasi belajar siswa yang rendah menjadi salah satu permasalahan dalam pembelajaran geografi. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh model creative problem solving terhadap kemampuan memecahkan masalah dan motivasi belajar pada mata pelajaran geografi di SMA Islam Kepanjen. Jenis penelitian ini ialah eksperimen semu (quasi experiment) dengan rancangan pretest dan posttest control group design yang meliputi kelas X-2 dan X-4, pengambilan sampel secara purposive sampling. Analisis data yang digunakan ialah uji prasyarat serta uji hipotesis. Uji hipotesis dilaksanakan dengan menggunakan Uji MANOVA (Multivariate Analysis of Variance). Berdasarkan hasil analisis, nilai rata-rata kelas eksperimen lebih tinggi daripada nilai kelas kontrol. Hasil uji MANOVA memperlihatkan bahwasannya nilai F untuk Pillai's trace, Wilks' lambda, Hotelling's trace, dan Roy’s Largest Root mempunyai nilai yang sama, artinya hipotesis nol (Ho) ditolak serta hipotesis alternatif (Ha) diterima. Temuan pada penelitian ini adalah sintaks model creative problem solving yaitu problem finding, ide finding dan solution finding berpengaruh terhadap kemampuan memecahkan masalah dan motivasi belajar. Kesimpulan penelitian ini menunjukkan terdapat pengaruh model pembelajaran creative problem solving secara signifikan terhadap kemampuan memecahkan masalah dan motivasi belajar siswa yang diberikan perlakuan dan siswa dengan model pembelajaran konvensional.